2018
DOI: 10.3390/electronics7120342
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Wireless Sensor Network for Air Quality Measurements

Abstract: This study addresses the development of a wireless gas sensor network with low cost, small size, and low consumption nodes for environmental applications and air quality detection. Throughout the article, the evolution of the design and development of the system is presented, describing four designed prototypes. The final proposed prototype node has the capacity to connect up to four metal oxide (MOX) gas sensors, and has high autonomy thanks to the use of solar panels, as well as having an indirect sampling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
(33 reference statements)
0
28
0
Order By: Relevance
“…Generally, WSN is composed of tiny devices or nodes having an important role in collecting information by sensors from the environment as well as wirelessly communicating with other nodes in the system [174]. It has been indicated that in the development strategies of the WSN system, ZigBee, a wireless standard based on the IEEE 802.15.4 specification, is regarded as the most reliable communication protocol because of its low cost, low consumption, and low data rate [187,188]. In addition, use of the ZigBee protocol allows networks to work in power-saving mode [189,190].…”
Section: Wireless Sensor Network (Wsn)-based Systemsmentioning
confidence: 99%
“…Generally, WSN is composed of tiny devices or nodes having an important role in collecting information by sensors from the environment as well as wirelessly communicating with other nodes in the system [174]. It has been indicated that in the development strategies of the WSN system, ZigBee, a wireless standard based on the IEEE 802.15.4 specification, is regarded as the most reliable communication protocol because of its low cost, low consumption, and low data rate [187,188]. In addition, use of the ZigBee protocol allows networks to work in power-saving mode [189,190].…”
Section: Wireless Sensor Network (Wsn)-based Systemsmentioning
confidence: 99%
“…Therefore, there is a need for small, low-power devices for personal air quality monitoring. As a result, different small, portable, and low-power devices have emerged [5][6][7][8][9][10]. While these devices are less accurate and show a higher uncertainty compared with reference systems, they increase the spatial density of measurements and could provide useful information to citizens.…”
Section: Introductionmentioning
confidence: 99%
“…At base station, the sensed signal is demodulated. The proposed system is tested for humic acid water at 2.5 GHz frequency [13].A wireless sensor network having four metal oxide gas sensors powered by a solar panel to discriminate four volatile compounds, such as benzene, toluene, ethylbenzene, and xylene (BTEX) has been proposed in [14]. Pattern recognition of data is carried out by a radial basis neural network and principal component analysis.…”
Section: The Present Issuementioning
confidence: 99%